New drugs and new toxicities: pembrolizumab-induced myocarditis. (23rd January 2018) - Inayat, Faisal; Masab, Muhammad; Gupta, Sorab; Ullah, Waqas
Abstract : Pembrolizumab is an immune checkpoint inhibitor that significantly improves clinical outcomes in numerous solid organ malignancies. Despite successful therapeutic responses, this new drug comes with a constellation of adverse reactions. Herein, we chronicle the case of a patient with metastatic non-small-cell lung cancer treated with pembrolizumab. After two cycles, he developed new-onset dyspnoea on exertion. Electrocardiogram showed idioventricular rhythm with diffuse ST-segment elevations. Echocardiography revealed severe biventricular cardiac dysfunction. Based on diagnostic workup and exclusion of probable aetiologies, the patient was diagnosed with pembrolizumab-induced myocarditis. The treatment was initiated with corticosteroids and guideline-conform heart failure therapy. He demonstrated a marked clinical response with resolution of congestive heart failure symptoms. This article summarises the clinical evidence regarding the epidemiology, pathophysiology, clinical features, diagnostic modalities and management of patients with pembrolizumab-associated myocarditis. In addition, it highlights that programmed death receptor-1 inhibition can cause a spectrum of autoimmune adverse events requiring clinical monitoring and periodic screenings.